Effectiveness of problem-based learning strategies compared to conventional anatomy teaching approaches - Quratulain Javaid; Ambreen Usmani (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the effectiveness of problem-based learning compared to conventional teaching strategies, and to determine the impact of sub-disciplines of Anatomy on learning outcomes of the subject. Method: The cross-sectional, descriptive study was conducted at Bahria University Health Sciences, Karachi, from August to October 2022, and comprised 1st and 2nd year medical students and 1st year dental students of either gender who were being taught by the hybrid method including both conventional and problem-based learning strategies. Data was collected using a questionnaire circulated through Google Forms. It had close-ended questions that were scored on a Likert scale. Anatomy sub-disciplines explored were gross, embryology and histology. Data was analysed using SPSS 23. Results: Of the 251 subjects, 125(49.8%) were males and 126(50.2%) were females. The overall age ranged aged 18-23 years. There were 115(45.8%) 1st year medical students, 111(44.2%) 2nd year medical students and 25(10%) 1st year dental students. Among 1st year medical students 60(52.17%), among 2nd year medical students 64(57.6%) and among 1st year dental students 14(56%) respondents favoured problem-based learning compared to conventional methodology. Highly significant results were obtained regarding need of topic revision (p<0.001), whether knowledge of conventional teaching method is enough for understanding the clinical scenarios (p=0.017, whether pictures shown during the problem-based learning sessions were enough for understanding anatomy (p=0.035), relevance of questions in oral structured practical examination (p=0.019) and viva (p=0.002). When the participants were asked regarding the anatomy sub-discipline that required revision for comprehensive learning, 72(28.3%) mentioned gross anatomy. Conclusion: Students considered problem-based learning to be more inducive in enhancing learning compared to conventional teaching. Key Words: Problem-based learning strategies, Conventional anatomy, Teaching approaches.